Differences of Career Decision Making in Senior High School’s Student Based on Gender - Anita Wulandari; Herman Nirwana (Jurnal Neo Konseling, 2019)
This study aims to (1) describe male students’s career decision making, (2) describe female students’s career decision making, and (3) examine differences in career decision making of Senior High School’s student by gender. This study uses a comparative descriptive analysis. The  population in this study were all students of class X, XI, and XII SMA and the amount of samples was 134 students taken using census techniques (non probability sampling). This study uses two data analysis techniques, descriptive analysis and different tests. Descriptive analysis is using the percentage formula. While differences analysis uses the independent samples t test formula and the calculation is assisted by using the SPSS version 20 for windows. The result of the study showed (1) the level of career decision making for male students are in good category, (2) the level of career decision making for female students are in good category, and (3) there was significant difference in career decision making of students’s career decision making base on gender with a correlation coeficient of 0,736 and a significance level of 0,021.